2014
DOI: 10.1016/j.urology.2014.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Seminal BAX and BCL2 Gene and Protein Expressions in Infertile Men With Varicocele

Abstract: Seminal BAX is significantly increased and seminal BCL2 is significantly decreased in men associated with Vx. Seminal BAX is significantly increased in men associated with bilateral Vx compared with unilateral Vx and in cases with Vx grade III compared with Vx grade I and II cases. Seminal BAX demonstrates significant negative correlation with sperm concentration, sperm motility, and sperm normal forms, whereas seminal BCL2 demonstrates significant reverse positive correlations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 18 publications
2
40
0
Order By: Relevance
“…Many pathways result in testicular apoptosis, and these processes appear to be regulated by the plasma membrane externalisation of negatively charged membrane phosphatidylserine, mitochondrial dysfunction, chromatin condensation and DNA fragmentation (Ku, Shim, Kim, & Paick, ; Mostafa, Rashed, Nabil, & Amin, ). Granulysin structure suggests a potential mechanism of action; the positive charges of granulysin appear to attract the molecule towards the negatively charged surface cells (Smyth et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Many pathways result in testicular apoptosis, and these processes appear to be regulated by the plasma membrane externalisation of negatively charged membrane phosphatidylserine, mitochondrial dysfunction, chromatin condensation and DNA fragmentation (Ku, Shim, Kim, & Paick, ; Mostafa, Rashed, Nabil, & Amin, ). Granulysin structure suggests a potential mechanism of action; the positive charges of granulysin appear to attract the molecule towards the negatively charged surface cells (Smyth et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Cocuzza et al (2012) pointed that as Vx grade increased, seminal reactive oxygen species increases and sperm concentration decreases. Mostafa et al (2012Mostafa et al ( , 2014 pointed that seminal OS is related to increased Vx grade in infertile OAT men associated with Vx.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, various molecular mechanisms have been proposed for elucidating apoptosis in germ cells. The study in the Bcl‐2 apoptotic family indicated that seminal Bcl‐2 demonstrated a positive correlation with sperm concentration and sperm motility in infertile men with varicocele, whereas Bax demonstrated a negative correlation (Mostafa, Rashed, Nabil, & Amin, ). Nuclear factor‐kappa B (NF‐κB), a key regulator of the inflammatory gene, was reported to be involved in varicocele‐induced testicular dysfunction (Tuğcu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the character of the 14‐3‐3 protein, analysing the binding partners of 14‐3‐3ε may help reveal the mechanism of germ cell apoptosis. Some notable studies have suggested that Bcl‐2 family proteins play an important role during germ cell apoptosis in rats and humans (Lee, Lee, Cheng, & Jeng, ; Mostafa et al, ). 14‐3‐3 protein protected cell apoptosis by binding pro‐apoptotic proteins such as Bax and Bad (Nomura et al, ; Rapp, Fischer, Rennefahrt, Hekman, & Albert, ).…”
Section: Discussionmentioning
confidence: 99%